1980
DOI: 10.1113/jphysiol.1980.sp013136
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alimentary infusions of glucose, amino acids, or neutral fat on meal size in hungry pigs.

Abstract: SUMMARY1. Young growing pigs trained to press a panel in order to obtain delivery of small quantities of food were adapted to eating all their food during one readily measured meal per day.2. Twenty-nine pigs were surgically fitted with an exteriorized cannula connected to either (a) the stomach or (b) the duodenum.3. Two pigs were each fitted with two cannulae in the duodenum which were exteriorized and connected outside the body. Food was then shunted so as to pass along outside the body from the pyloric reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 24 publications
(19 reference statements)
1
17
0
Order By: Relevance
“…0.6-0.8-fold in the baboon; Woods et al 1984) and are less effective than the equivalent gastrointestinal infusions (e.g. pig; Stephens, 1980). Using sham-fed rats, glucose infusions into the small intestine have now been shown to inhibit intake physiologically by eliminating intestinal signals from the digesta, the threshold rate of infusion for intestinal inhibition of satiety (0.46 kJ (0.11 kcal)/min) being less than the normal rate of emptying (1.34 kJ (0.32 kcal)/min; Reidelberger et al 1983).…”
Section: S T O M a C H Control O F Intakementioning
confidence: 99%
“…0.6-0.8-fold in the baboon; Woods et al 1984) and are less effective than the equivalent gastrointestinal infusions (e.g. pig; Stephens, 1980). Using sham-fed rats, glucose infusions into the small intestine have now been shown to inhibit intake physiologically by eliminating intestinal signals from the digesta, the threshold rate of infusion for intestinal inhibition of satiety (0.46 kJ (0.11 kcal)/min) being less than the normal rate of emptying (1.34 kJ (0.32 kcal)/min; Reidelberger et al 1983).…”
Section: S T O M a C H Control O F Intakementioning
confidence: 99%
“…Glucose, but not amino acids or fat solutions, when injected into the duodenum of fasted pigs had a depressing effect on food intake, suggesting a chemical effect of glucose in addition to the osmotic or stretch effects of this type of treatment (Stephens, 1980); again, this is blocked by vagotomy (Stephens & Heron, 1979). Glucose solution given into the duodenum of free-feeding chickens had much less effect on intake than did solutions of mannitol or potassium chloride (which are not absorbed) of the same osmolality (Shurlock & Forbes, 1981a), supporting the idea of osmotic or stretch effects.…”
Section: Visceral Influencesmentioning
confidence: 99%
“…Furthermore, in contrast to the lack of effect of rapid gastric injections of glucose (Stephens, 1980 a) slow gastric infusions of glucose similarly inhibited intake according to both the energy content and osmotic concentration. Unlike in the rat (Deutsch & Gonzalez, 1980;Koopmans, 1983) these latter effects were largely inhibited by duodenal perfusion with the local anaesthetic lignocaine and thus cannot be of purely gastric origin.…”
Section: Discussionmentioning
confidence: 77%
“…Therefore even though blood glucose levels rise rapidly with feeding (Anderson, 1974;Rayner, Weekes & Bruce, 1981) it appears that glucose has no post-absorptive effects on short-term intake and that any influence of dietary carbohydrate must be pre-absorptive. Indeed a number of studies have shown that rapid injection of glucose into the duodenum during or immediately prior to feeding does suppress intake in the pig (Heron & Stephens, 1978;Houpt et al 1979; Stephens, 1980 a;Houpt, Baldwin & Houpt, 1983 a), an effect that appears to depend upon the osmotic concentration of the glucose (Houpt et al 1979(Houpt et al , 1983a. None of these studies reported the response to glucose on an energy basis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation